Far from the Madding Crowd - Hardy, Thomas (England Penguin Books Ltd., 1979)
This story of a proud rural beauty and the three men who court her is the novel that first made Thomas Hardy famous.
Include Chronology and Notes.
Keywords: England--Wessex -- Women farmers -- England